Proceedings of the 50th Annual IEEE/ACM International Symposium on Microarchitecture 2017
DOI: 10.1145/3123939.3123977
|View full text |Cite
|
Sign up to set email alerts
|

Drisa

Abstract: Data movement between the processing units and the memory in traditional von Neumann architecture is creating the "memory wall" problem. To bridge the gap, two approaches, the memory-rich processor (more on-chip memory) and the compute-capable memory (processing-in-memory) have been studied. However, the rst one has strong computing capability but limited memory capacity/bandwidth, whereas the second one is the exact the opposite. To address the challenge, we propose DRISA, a DRAM-based Recongurable I n-Situ A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 250 publications
(6 citation statements)
references
References 68 publications
(72 reference statements)
0
6
0
Order By: Relevance
“…An insitu accelerator DRISA with large internal memory bandwidth and high computing performance was proposed to address this problem. [22] Experimental results showed that DRISA achieved significant performance improvement in convolutional neural network inference acceleration compared to state-of-the-art systems (ASICs and GPUs).…”
Section: Logic Computingmentioning
confidence: 98%
See 2 more Smart Citations
“…An insitu accelerator DRISA with large internal memory bandwidth and high computing performance was proposed to address this problem. [22] Experimental results showed that DRISA achieved significant performance improvement in convolutional neural network inference acceleration compared to state-of-the-art systems (ASICs and GPUs).…”
Section: Logic Computingmentioning
confidence: 98%
“…The memory cell stores digital binary values represented by the retained charge or device resistance. [21][22][23] By configuring the reference voltage (V ref ) of SAs, different Boolean functions can be implemented. This operating scheme is not a fully inmemory computation to a certain extent, as it requires the cooperation of peripheral circuits to convert the computing results.…”
Section: Nonvolatile Memory Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9][10][11] LIM comprising SRAM or DRAM arrays has demonstrated relatively high reliability, high computation speed, and low operating voltage compared to RRAM-or MRAM-based LIM. [12][13][14][15][16] Recently, feedback field-effect transistors (FBFETs) that operate via positive feedback (PF) loop mechanisms have attracted DOI: 10.1002/aelm.202300132 attention for LIM. [17][18][19][20] PF loops are generated or eliminated in the channels because of the recursive mutual interaction between the carrier injection and potential barriers.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5]33] Various memory devices, including resistive random-access memory (RRAM), magnetoresistive RAM (MRAM), static RAM (SRAM), and dynamic RAM (DRAM), have been widely researched for developing LIM. [5][6][7][8][9][10][11][12][13][14][15][16] Particularly, LIM composed of RRAM or MRAM has performed stateful logic operations via voltage division between the devices and resistors. [6][7][8][9][10][11] LIM comprising SRAM or DRAM arrays has demonstrated relatively high reliability, high computation speed, and low operating voltage compared to RRAM-or MRAM-based LIM.…”
Section: Introductionmentioning
confidence: 99%